The Arthurian way of death : the English tradition - Cherewatuk, Karen; Whetter, K. S. (Kevin Sean), 1969- (Woodbridge, UK ; Rochester, N.Y. : D.S. Brewer, 2009)
It is arguably the tragic end to Arthur's kingdom which gives the myth its exceptional resonance and power. The essays in this volume explore the presentation of death and dying in Arthurian literature and film produced in England and America from the mid.
pt. 1. The early tradition in England. "But here Geoffrey falls silent" : death, Arthur, and the Historia regum Britannie / Siân Echard ; Mordred's sons / Edward Donald Kennedy ; Dying in Uncle Arthur's arms and at his hands / Karen Cherewatuk -- pt. 2. Middle English romance and Malory. "Hadet with an aluisch mon" and "britned to no[yogh]t [nowt]" : Sir Gawain and the Green Knight, death, and the devil / Michael W. Twomey ; Love and death in Arthurian romance / K.S. Whetter ; Death in the margins : dying and scribal performance in the Winchester manuscript / Thomas H. Crofts ; The legible corpses of Le morte Darthur / Michael Wenthe ; Malory and the death of kings : the politics of regicide at Salisbury Plain / Lisa Robeson ; "Layde to the colde erthe" : death, Arthur's knights, and narrative closure / Cory James Rushton -- pt. 3. Medieval influence and the modern Arthuriana. Arthurian exits : alone, together, or none of the above / Janina P. Traxler ; Woman as agent of death in Tennyson's Idylls of the king / James Noble ; Death as 'neglect of duty' in Howard Pyle's The story of the Grail and the passing of Arthur / Julie Nelson Couch ; Death and the "grimly voice" in David Jones's In parenthesis / Samantha Rayner ; Roll the final credits : some notes on cinematic depictions of the death of Arthur / Kevin J. Harty.
Text in English; Some passages in Middle English.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Arthur, -- King -- Death and burial -- Legends -- History and criticism; Arthur, -- King; Arthurian romances -- History and criticism; Death in literature; Arthurian romances in motion pictures; Death in motion pictures; Cycle d'Arthur -- Histoire et critique; Mort dans la littérature.; Cycle d'Arthur au cinéma.; Mort au cinéma.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; HISTORY -- Medieval; Arthurian romances; Arthurian romances in motion pictures; Death in literature; Death in motion pictures; Electronic books; Criticism, interpretation, etc